If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 3 = 7x + -9 Reorder the terms: 3 + 8x = 7x + -9 Reorder the terms: 3 + 8x = -9 + 7x Solving 3 + 8x = -9 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 3 + 8x + -7x = -9 + 7x + -7x Combine like terms: 8x + -7x = 1x 3 + 1x = -9 + 7x + -7x Combine like terms: 7x + -7x = 0 3 + 1x = -9 + 0 3 + 1x = -9 Add '-3' to each side of the equation. 3 + -3 + 1x = -9 + -3 Combine like terms: 3 + -3 = 0 0 + 1x = -9 + -3 1x = -9 + -3 Combine like terms: -9 + -3 = -12 1x = -12 Divide each side by '1'. x = -12 Simplifying x = -12
| y^2-7y+4=0 | | 1/3(x+2)=6 | | 1/5(x+5)=-3 | | 3x+14=18-5x | | -1/3(x+5)=-10 | | 5x^2=-28x-15 | | 26()45x()56x=30 | | -1/3(x+3)=-9 | | -1/5(x+2)=8 | | x:(0,001)=38 | | 6x+30=5x-36 | | x:(-0,01)=38 | | z+29/3+z+23/7=12 | | 12=4x-1.5 | | x-5y=12fory | | x-45/5+x+10/2=-4 | | (6x^2+20x+6)-(6x^2-3x-3)= | | 5/11x=15 | | y+1=-1(x+10) | | ?4/49= | | -4(5y+w)-(-2w+y)= | | 4e-18=-2(e+3) | | 3(x-6)=-27 | | x^2-7x-198=0 | | 20=7x+9/4+5x+9/8 | | 2x+3=5-(7x-8) | | 13=9/5c+32 | | 2b^2+12b=14 | | 4(x-1)-3=-23 | | 3x^2-30x+85=0 | | 15-4+6=13 | | (1/14)/420 |